Upaya Meningkatkan Hasil Belajar Matematika Dengan Model Pembelajaran Make a Match Siswa SMP Muhammadiyah 2 Tidore Kepulauan - Sarni Dahlan; Jafar Dahlan (Jurnal Ilmiah Wahana Pendidikan, 2023)
In learning numbers and mathematical operations for class VII students of Muhammadiyah Middle School, Tidore Islands City, there are still many who get scores below the KKM (KKM 70), especially in solving questions related to mathematical problems. Therefore, efforts are needed to improve mathematics learning outcomes. This research aims to determine the improvement in learning outcomes of class VII students of Muhammadiyah Middle School, Tidore Islands City, Academic Year 2019/2020 in completing questions on the main material of numbers and mathematical operations through the implementation of the make a match cooperative learning model. The research subjects were 29 class VII students of Muhammadiyah Middle School, Tidore Islands City. The data collected includes student learning outcomes, teacher observation results, and student observation results. This research is Classroom Action Research (PTK) which is carried out in two cycles. Each cycle includes 4 (four) stages, namely planning, implementing actions, observation, and reflection. In this study, it is said to be successful if at least 85% of students get a score ≥ 70. The research results showed: (1) Student learning completeness in cycle I was 68.96% with an average score of 70.27 and in cycle II it was 86.75% with an average score of 80.65. The data above, clearly shows that in cycle I the learning outcomes did not meet expectations, which means the indicators of success have not been achieved, while in cycle II the learning outcomes were in line with expectations, which means the indicators of success have been achieved